IMPLEMENTASI PASAL 277 UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN TERHADAP ANGKUTAN BARANG YANG OVERDIMENSI DI WILAYAH KABUPATEN KAMPAR - Aprianti, Gusni; Effendi, Erdianto; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Overdimensional vehicle is a vehicle modified which is conducted by people top workshop basic request from the vehicle owner this overdimensional vehicle modified body height and width plus aims to be able to transport loads which uses less cost. The formulation of the problem in this research is how is the implementation of Article 277 of Law Number 22 Year 2009 concerning Road Traffic and Transportation in the Kampar District Region, and what are the obstacles and efforts to implement Article 277 of Law Number 22 Year 2009 Concerning Traffic and Road Transportation in the Kampar District Region. This research is classified into sociological legal research viz approach the problem under study with the nature of the real law or in accordance with the reality of life in society, this study wants to see the correlation between law and society so that it reveals the effectiveness of law enforcement in society.Implementation of Article 277 of Law Number 22 Year 2009 concerning Road Traffic and Transportation, the sanctions provided for in article 277 have never been applied, So far, in Kampar regency, vehicles that are overdimensional when they are caught in raids are only given tickets or administrative sanctions. Obstacles and efforts to implement Article 277 of Law Number 22 Year 2009 Concerning Traffic and Road Transportation in the District of Kampar, many vehicle owners don't know that overdimensional vehicles can endanger the lives of others, and they don't know much about the rules governing overdimensional vehicles, many vehicle owners who depend on their vehicle for their needs, that is what makes it difficult for law enforcers to apply article 277. The first attempt is to explain or provide socialization to vehicle owners and drivers about overdimensional vehicles and also to explain anything caused by overdimensional vehicles, good cooperation between the transportation department and the police, and impose strict sanctions on vehicle owners who have recorded their vehicles several times.Keywords: Implementation - Overdimensions - Freight Transport